2018
DOI: 10.1016/j.jmatprotec.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Creep behaviour of inconel 718 processed by laser powder bed fusion

Abstract: Additive manufacturing lends itself well to the manufacture of aerospace parts due to the high complexity and small volume of many components found in modern aero engines. By exploiting additive manufacturing design freedoms, enhanced part functionality can be achieved and lead time can be reduced. However, the integrity of these parts is a primary concern which often cannot be guaranteed with current generation additive manufacturing methods and materials. Studies on the performance of additively manufactured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 32 publications
5
23
0
Order By: Relevance
“…So that the two-bar specimen can be easily machined and provide information on all three creep stages with fewer materials. This is consistent with the authors' previous study in which the creep testing experimental arrangement of LPBF specimens was determined [22]. Figure 2 shows a schematic of the testing strategy for this study.…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…So that the two-bar specimen can be easily machined and provide information on all three creep stages with fewer materials. This is consistent with the authors' previous study in which the creep testing experimental arrangement of LPBF specimens was determined [22]. Figure 2 shows a schematic of the testing strategy for this study.…”
Section: Methodssupporting
confidence: 89%
“…The temperature for the testing was 650˚C which is also the phase transformation temperature for the main strengthening particles, i.e. γ'' phase, in Inconel 718 [4], this is also consistent with the previous study [22].…”
Section: Figure 4 Tensile Testing Of As-built Tbs Specimens To Verify Loading For Creep Testingsupporting
confidence: 89%
See 1 more Smart Citation
“…The microstructural analysis was performed on the horizontal (XY) and vertical (ZX) reference faces of the cubic specimens ( Figure 1a). All the specimens were polished LPBF Stress-relief Annealing [29] Temperature, ᵒC Hot isostatic pressing [33] Time For this study, it was decided to carry out both treatments at the same temperature in the 1100-1150 • C range. This decision can be explained by the fact that HIP at this temperature had already been successfully used to reduce processing-induced porosity, and to homogenize and recrystallize LPBF-built microstructures [16,24,34].…”
Section: Methodsmentioning
confidence: 99%
“…Unlike IN625 alloy, LPBF IN718 alloy, as a precipitation-hardened alloy with a higher mechanical resistance at elevated temperatures [25], has been covered by many studies [26][27][28][29][30]. It was shown that LPBF IN718 alloy manifested a high build-orientation-related anisotropy of its creep properties, caused by preferentially oriented distributions of dendrites and precipitations formed during LPBF processing [26].…”
Section: Introductionmentioning
confidence: 99%